Comparative study of magnetoelectric BaTiO3–Co0.8Zn0.2Fe2O4 bi-tunable ceramics sintered by Spark Plasma Sintering and classical method. Issue 18 (15th December 2019) - Ciomaga, Cristina E.; Guzu, Alexandra; Airimioaei, Mirela; Curecheriu, Lavinia P.; Lukacs, Vlad Alexandru; Avadanei, Ovidiu G.; Stoian, George; Grigoras, Marian; Lupu, Nicoleta; Asandulesa, Mihai; Mitoseriu, Liliana
Abstract: Di-phase 0.66BaTiO3 –0.33Co0.8 Zn0.2 Fe2 O4 ceramic composites with randomly mixed phases have been obtained by conventional sintering method (CM) and Spark Plasma Sintering (SPS). The impact of sintering method on the structural, microstructural and functional properties is comparatively analysed. The dielectric properties are dominated by the BaTiO3 phase, with contributions from the interfaces mostly on the dielectric relaxation properties, while the ferrimagnetic character of the composite is derived from the ferrite phase as a sum property. Both CM and SPS ceramics show bi-tunable character, i.e. their permittivity can be modified by the application of both electric and magnetic fields. A high dielectric nonlinearity is mostly characteristic to the ceramics with larger grains. The electrical tunability tends to reduce by the application of a magnetic field an almost is cancelled in the SPS ceramic. The two types of ceramics show opposite signs of their magnetocapacitance properties, indicating that they have different origins. A microwave filter realised with these two types of ceramics have been tested. With increasing magnetic field from 0 to 1.9 kOe (above the magnetic coercive field), the resonance frequency can be up/down shifted, as result of the positive/negative magnetoelectric coupling.